ZERO-INFLATED POISSON REGRESSION TO DETERMINE THE FACTORS THAT INFLUENCE THE MATERNAL MORTALITY RATE IN BANDUNG 2016 - Sri Rahayu; Nurul Gusriani; Iin Irianingsih (Universitas Jenderal Soedirman, 2018)
In Indonesia, especially Bandung, there are still many cases of maternal deaths during pregnancy, birth, and postpartum which can increase the Maternal Mortality Rate (MMR). Cases of maternal deaths are mostly due to exsanguination, infection, anemia, and the other causes that related to pregnancy. To reduce the MMR of Bandung, we can analyze to determine the factors that influence the MMR in order to maximize the maternal health care programs so as to prevent the possibility of death. The analysis is using Zero-Inflated Poisson (ZIP) regression because maternal mortality data is the result of counting that allows overdispersion due to excess zeros. Regression parameter estimation use expectation maximization algorithm followed by the Newton-Raphson iteration method. The analysis result showed that of the five suspected factors to affect the MMR -such as the first tetanus toxoid immunization (TT1), the provision of 90 Fe tablets (Fe3), postpartum care, pregnancy complications, and the first antenatal care (K1)- only TT1 and postpartum care are significantly affect the MMR.